Aldosterone and cortisol synthesis regulation by angiotensin-(1-7) and angiotensin-converting enzyme 2 in the human adrenal cortex. Issue 8 (August 2021) - Caroccia, Brasilina; Vanderriele, Paul-Emmanuel; Seccia, Teresa Maria; Piazza, Maria; Lenzini, Livia; Prisco, Selene; Torresan, Francesca; Domenig, Oliver; Iacobone, Maurizio; Poglitsch, Marko; Rossi, Gian Paolo
Abstract : Objective: The branch of the renin--angiotensin system constituting angiotensin-(1–7) [Ang-(1–7)], the Ang II type 2 receptor, the Mas receptors and the Ang-(1–7)-forming enzyme ACE-2, by counteracting the Ang II type 1 receptor (AT1R)-mediated effects, are held to be cardiovascular protective in several conditions. However, whether Ang-(1–7) and ACE-2 are detectable in human adrenocortical tissues and whether they affect aldosterone and cortisol biosynthesis was unknown. Methods: We measured angiotensin peptides with liquid chromatography tandem-mass spectrometry and ACE-2 mRNA with digital droplet (dd)PCR in human aldosterone-producing adenoma (APA) and APA-adjacent tissue obtained from patients with primary aldosteronism. We also investigated the effects of Ang-(1–7) and the ACE-2 activator diminazene aceturate (DIZE) on aldosterone synthase ( CYP11B2 ) and 11β-hydroxylase ( CYP11B1 ) gene expression, in the absence or presence of the AT1R antagonist irbesartan, or of the MasR antagonist A779. Results: APA and APA-adjacent adrenocortical tissues express ACE-2 mRNA and contain detectable amounts of Ang II and Ang-(2–8), but not of Ang I, Ang-(1–5), Ang (3–8) and Ang-(1–7). Under unstimulated and Ang II- stimulated conditions Ang-(1–7) did not blunt CYP11B1 and CYP11B2 mRNA. At supraphysiological concentrations (10 −4  mol/l), Ang-(1–7) stimulated both CYP11B1 and CYP11B2 mRNA via the AT1R. The ACE-2 activator DIZE increased by 1.5-fold ACE-2 mRNA but did not blunt Ang II- upregulated CYP11B1 and CYP11B2 expression. Conclusion: These results do not support the hypothesis that the ACE-2/Ang-(1–7)/MasR axis play a protective role by counteracting enhanced aldosterone secretion in humans. Abstract : Supplemental Digital Content is available in the text